PERSEPSI MASYARAKAT TERHADAP PENTINGNYA PENDIDIKAN TINGGI UNTUK KAUM PEREMPUAN (Studi Kasus di Desa Curahdringu Kecamatan Tongas Kabupaten Probolinggo) - Faiqotus Silvia Nabila; jakaria umro (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
Every citizen has the right to obtain education to higher education regardless of gender. However, in tertiary education for women there is still overlapping, because of the nature of women in the kitchen. Therefore there must be awareness from the public in viewing higher education for a woman. This study aims to describe the condition of women's education, describe the views of the community towards women with high education and describe the community's perception of the importance of higher education for women in Curahdringu Village, Tongas, Probolinggo. This research is a qualitative descriptive study. The subject of this research is the community, the data collection methods in this study are observation, interviews and documentation. Data sources used in this study are primary data sources and secondary data sources. The results obtained from this research: The condition of the education of women in the Curahdringu Village is predominantly pesantren graduates and women born in the 70s-80s on average only graduate from elementary school. However, now it has experienced developments with the construction of educational facilities and now there are female girls in Curahdringu Village starting to continue to university lecture, Society positively views highly educated women and hopes that they can apply their knowledge to society and There are still societies that perceive women as not important to be highly educated on the grounds of their nature in the kitchen, but many people who perceive higher education are important to women because someday they will become educators for their children.